Looks matter? Field performance and farmers' preferences for drought-tolerant maize in Kenya - Kramer, Berber; Wellenstein, Hailey; Waweru, Carol; Kivuva, Benjamin (Elsevier, 2025)
Context To help farmers adapt to climate change, breeding programs have developed drought-tolerant (DT) maize varieties, but varietal turnover among smallholder farmers is slow. One possible reason for low adoption is that DT varieties produce higher yields than older hybrid maize varieties but are not visibly more drought tolerant, especially if morphology is a factor in farmers' varietal choice.